PWE-091 Limited Impact on Colorectal Cancer Detection and Mortality Rates with Complete Colonoscopy Examination Despite Poor Bowel Preparation. (17th August 2016) - Masding, A; Cargill, Z; Aveyard, N; Musa, S; Alisa, A; Tang, K
Abstract : Introduction: Achieving key quality indicators of colonoscopy are recognised to be associated with quality of bowel cleansing. 1 However, the impact of bowel preparation quality on colorectal cancer (CRC) detection and associated mortality rates is unclear. Limited published studies report conflicting results correlating detection of pre-malignant lesions with quality of bowel preparation and do not report on colorectal mortality. 2 Current guidelines suggest that if bowel preparation is poor, colonoscopy should be repeated within 1 year. 3 Aim: To determine the prevalence of poor bowel preparation in patients achieving complete colonoscopy, and its association with polyp detection, CRC, and mortality rates within a large district general hospital. Methods: All patients with poor bowel preparation (Boston Bowel Preparation Scale <5) undergoing colonoscopy by a single endoscopist were identified using the UNISOFT database over 5 years (2006–2010). Electronic records were analysed to identify indication for colonoscopy, completion rates, adenoma detection rate (ADR), diagnosis, 1 and 5 year mortality rates, and number of repeat colonoscopies/completion CT colonography. Results: 990 colonoscopies were performed (ADR 26%). 208/990 (21%) had poor bowel preparation (M:F 103:105, mean age 62 years). Of these, 197/208 (95%) had complete colonoscopy to the terminal ileum, caecum or anastomosis and 51/208 (25%) underwent repeat colonoscopy/CT colonography. 86/208 (41%) had indications of anaemia, previous polyps, previous CRC and abnormal imaging. Of these, 9% (n = 8/86) were found to have CRC. There was a 3/86 (3.5%) 1 year mortality rate, and 24/86 (28%) 5 year mortality rate, none from CRC. In a comparison group with the same indications for colonoscopy and good bowel preparation (n = 69), 1 and 5 year mortality rates were 2.9% (2/69) and 7.3% (n = 5/69), respectively, 1 of which resulted from CRC. Conclusion: The quality of bowel preparation does not significantly impact on CRC detection or mortality rates if complete colonoscopy examination is achieved. Early repeat colonoscopy/CT colonography within 1 year may not be necessary and subsequent examination could be at the standard recommended surveillance interval. References: 1 Hassan, et al . Bowel preparation for colonoscopy: ESGE Guideline. Endoscopy 2013;45 :142–150. 2 Wong, et al . Determinants of Bowel Preparation Quality and Its Association With Adenoma Detection. Medicine (Baltimore) 2016;95 (2). 3 Lieberman, et al . 2012. Guidelines for colonoscopy surveillance after screening and polypectomy: a consensus update by the us multi-society task force on colorectal cancer. Gastroenterology 143 (3):844–57. Disclosure of Interest: None Declared